2004
DOI: 10.1021/bp034334e
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Gas-Phase Reactions by Increasing the Long-Term Stability of the Catalyst

Abstract: Enzymatic gas-phase reactions are usually performed in continuous reactors, and thus very stable and active catalysts are required to perform such transformations on cost-effective levels. The present work is concerned with the reduction of gaseous acetophenone to enantiomerically pure (R)-1-phenylethanol catalyzed by solid alcohol dehydrogenase from Lactobacillus brevis (LBADH), immobilized onto glass beads. Initially, the catalyst preparation displayed a half-life of 1 day under reaction conditions at 40 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Obviously, sucrose occupies the adsorption sites on the support material and consequently less sites on the support are available for protein binding. Ferloni et al (6) have shown that enzyme preparations prepared with sucrose have markedly improved stability under reactive gas phase conditions.…”
Section: Effect Of Drying Conditions On Immobilization Efficiency Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, sucrose occupies the adsorption sites on the support material and consequently less sites on the support are available for protein binding. Ferloni et al (6) have shown that enzyme preparations prepared with sucrose have markedly improved stability under reactive gas phase conditions.…”
Section: Effect Of Drying Conditions On Immobilization Efficiency Of mentioning
confidence: 99%
“…Unfortunately the operational instability of ADHs in aqueous solution limits their widespread industrial application (3,4). Application of ADHs in non-conventional media such as organic solvents and in a gas/solid system (enzymatic gas phase system) could overcome some of the problems associated with the ADH instability in aqueous media (5,6). However, the use of enzymes in powder form in non-conventional media may lead to mass transfer limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] In comparison, Trichothecium roseum is sensitive to the position and electronic effect of the substituent. Thus, the derivatives 1b-d and 1o-p did not afford the corresponding alcohols 2 ( Table 2, entries 2-4, and [13][14]; however, in contrast to this observation, Aspergillus niger and Alternaria alternata are not substrate structure-dependent reducers. While Trichothecium roseum exhibits R selectivity in all cases, Aspergillus niger and Alternaria alternata do not show any preference in enantioselectivity.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, it presents many advantages compared to other enzymatic systems (i.e., liquid, mono or biphasic ones): (i) mass transfers are more efficient at the solid/gas interface, (ii) isolated enzymes and cofactors are usually more stable due to a restricted water availability, (iii) problem of solubility of substrates and products do not exist, and (iv) the use of solvent can be avoided Legoy, 1993, 1995a). It has been used with enzymes such as lipases and esterases (Lamare and Legoy, 1993;Lamare et al, 2001), oxydo-reductases (Ferloni et al, 2004;Trivedi et al, 2006a,b), dehalogenases (Dravis et al, 2000(Dravis et al, , 2001, a lyase, and a decarboxylase (Spiess et al, 2007).…”
Section: Introductionmentioning
confidence: 99%